(untitled) - Nunan, David (Boston, 2005)
Practical English Language Teaching offers a thorough yet practical overview of language teaching methodology for teachers and teachers in preparation. The principles outlined in each chapter are richly illustrated with vignettes and extracts from real classrooms so the reader can see what the principles "look like" when realized in classroom teaching. The book is divided into three sections: Exploring Skills, Exploring Language, and Supporting the Learning Process.
Keywords: English language; Study and teaching